2017
DOI: 10.1038/s41467-017-00246-8
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal mucosal transmission of Zika virus in rhesus macaques

Abstract: Zika virus is present in urine, saliva, tears, and breast milk, but the transmission risk associated with these body fluids is currently unknown. Here we evaluate the risk of Zika virus transmission through mucosal contact in rhesus macaques. Application of high-dose Zika virus directly to the tonsils of three rhesus macaques results in detectable plasma viremia in all animals by 2 days post-exposure; virus replication kinetics are similar to those observed in animals infected subcutaneously. Three additional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Especially, some preliminary in vitro assays have also demonstrated that human respiratory cells are highly susceptible to ZIKV 33 . Additionally, a recent paper published during the submission of our manuscript has demonstrated that direct inoculation of high-dose ZIKV into the tonsils in rhesus macaques resulted in productive infection 34 . These combined findings from cell culture and animal model call attention to the potential risk of ZIKV transmission via oral or nasal routes, such as the consumption of contaminated food or breast milk, or via nasal routes, such as the inhalation of or contact with contagious droplets or aerosols.…”
Section: Discussionmentioning
confidence: 83%
“…Especially, some preliminary in vitro assays have also demonstrated that human respiratory cells are highly susceptible to ZIKV 33 . Additionally, a recent paper published during the submission of our manuscript has demonstrated that direct inoculation of high-dose ZIKV into the tonsils in rhesus macaques resulted in productive infection 34 . These combined findings from cell culture and animal model call attention to the potential risk of ZIKV transmission via oral or nasal routes, such as the consumption of contaminated food or breast milk, or via nasal routes, such as the inhalation of or contact with contagious droplets or aerosols.…”
Section: Discussionmentioning
confidence: 83%
“…Although saliva appears to be a useful sample to diagnose ZIKV infection during the acute phase, other studies have reported a low risk of transmission through this fluid [10,12,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Saliva from infected animals, despite containing viral RNA, does not appear to be capable of transmitting infection. 52 To further understanding of sexual transmission of ZIKV, vaginal, and rectal challenges have been used, 53,54 finding both routes are able to produce an infection measurable in serum ( Figure 3C), with dynamics that look very comparable to the subcutaneous infection route.…”
mentioning
confidence: 99%